2020
DOI: 10.1097/ico.0000000000002521
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Epithelial Thickness Profile Changes 18 Months After Photorefractive Keratectomy

Abstract: Purpose: Long-term evaluation of corneal epithelial thickness (ET) profile changes after photorefractive keratectomy (PRK) using Fourier-domain anterior segment optical coherence tomography. Methods: Three hundred twenty-six eyes of 163 patients were included in this prospective observational study. The corneal epithelial map was obtained across a 9-mm diameter area of the cornea before and up to 27 months after surgery. ET was assessed in 25 sectors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
2
7
2
Order By: Relevance
“…5,21 Using AS-OCT, we previously reported that in normal corneas, the mean (95% CI) epithelial thickness is 53.57 mm (53.16 to 53.98) centrally, which decreases with a low gradient of 0.43 mm toward 5.0 to 7.0 mm midperiphery and 2.31 mm toward 7.0 to 9.0 mm periphery. 22,23 Very similar results have been reported by other studies. 24,25 Therefore, contrary to what was said before, the 55 mm central and 65 mm peripheral epithelial ablation profile of the SCHWIND AMARIS laser system is not refractively neutral by targeting actual epithelial profile.…”
Section: Discussionsupporting
confidence: 90%
“…5,21 Using AS-OCT, we previously reported that in normal corneas, the mean (95% CI) epithelial thickness is 53.57 mm (53.16 to 53.98) centrally, which decreases with a low gradient of 0.43 mm toward 5.0 to 7.0 mm midperiphery and 2.31 mm toward 7.0 to 9.0 mm periphery. 22,23 Very similar results have been reported by other studies. 24,25 Therefore, contrary to what was said before, the 55 mm central and 65 mm peripheral epithelial ablation profile of the SCHWIND AMARIS laser system is not refractively neutral by targeting actual epithelial profile.…”
Section: Discussionsupporting
confidence: 90%
“…Golshan et al evaluated CET changes in patients who underwent PRK [ 48 ]. They found that in the first month after the procedure, CET decreased in all zones and only gradually thickened between 3 and 18 months, depending on the zone [ 48 ]. The highest thickening was noted in the paracentral area and the least in the central site [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that in the first month after the procedure, CET decreased in all zones and only gradually thickened between 3 and 18 months, depending on the zone [ 48 ]. The highest thickening was noted in the paracentral area and the least in the central site [ 48 ]. Sedaghat et al, in a group of 52 patients (52 eyes), reported CET thinning in the first month after PRK surgery, with gradual thickening at months 3 and 6 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in imaging technologies have allowed for a detailed characterization of epithelial remodeling in response to various corneal states. Different imaging modalities such as confocal microscopy,[ 6 7 ] very high-frequency (VHF) digital ultrasound,[ 8 9 10 ] and anterior segment optical coherence tomography (AS-OCT)[ 11 12 13 14 ] have been used to evaluate the corneal epithelium. AS-OCT can provide a map of corneal epithelial thickness over a 9 mm diameter of the cornea.…”
mentioning
confidence: 99%
“…Previous studies have shown significant epithelial remodeling over the ablation zone after myopic photorefractive keratectomy (PRK) surgery,[ 11 13 14 ] which is recognized as one of the reasons for postoperative refractive regression. [ 16 17 ] Several agents, such as anti-inflammatory drops and artificial lubricant tears, are routinely used after PRK to reduce the initial inflammation and alleviate patient discomfort after surgery, but little information is available on the effect of these agents on the corneal remodeling process.…”
mentioning
confidence: 99%